Comparison of dynamic visual acuity after implantation of toric bifocal or trifocal intraocular lens in age-related cataract patients: a randomized controlled trial - Li, Yuanting; Li, Xiaodan; Jiang, Xiaodan; Wang, Yuexin; Wu, Tingyi; Xia, Huaqin; Li, Xuemin (Frontiers in Neuroscience, 2023)
Purpose: To investigate the dynamic visual acuity (DVA) after implantation of toric bifocal or trifocal intraocular lens in age-related cataract patients. Methods: This was a prospective randomized controlled trial. Of one hundred and twenty-four patients enrolled and randomized to receive unilateral phacoemulsification and toric trifocal (939M/MP, Carl Zeiss Meditec AG, Jena, Germany) or toric bifocal (909M, Carl Zeiss Meditec AG, Jena, Germany) intraocular lenses (IOL) implantation, ninety-nine patients completed the follow-up and were included in final analysis. Postoperatively, uncorrected and corrected distance (UDVA and CDVA), intermediate (UIVA and DCIVA) and near (UNVA and DCNVA) static visual acuity, manifest refraction and uncorrected and corrected distance DVA (UDDVA and CDDVA) at 20, 40 and 80 degrees per second (dps) were evaluated at one week, one month and three months. Results: Three months postoperatively, the UDVA were 0.13 ± 0.11 and 0.14 ± 0.13 in the toric trifocal and bifocal IOL group, respectively. Significant better UIVA (trifocal, 0.17 ± 0.13 vs. bifocal, 0.23 ± 0.13, P = 0.037) and DCIVA (trifocal, 0.16 ± 0.11 vs. bifocal, 0.20 ± 0.12, P = 0.048) were observed in patients implanting toric trifocal than bifocal IOL at three months postoperatively. Patients implanted with toric bifocal IOL obtained better CDDVA at 80 dps (0.5607 ± 0.2032) than the trifocal group (0.6573 ± 0.2450, P = 0.039) at three months. Postoperative UDDVA and CDDVA at 20, 40 and 80 dps were significantly associated with age (P < 0.05, respectively) and postoperative static visual acuity (P < 0.05, respectively). Conclusion: Toric trifocal IOL provides better static intermediate visual acuity, and toric bifocal IOL implantation provides better distance dynamic visual acuity at high speed.